Neurons innervating both the central amygdala and the ventral tegmental area encode different emotional valences - Liu, Anqi; Cheng, Yuelin; Huang, Ju (Frontiers in Neuroscience, 2023)
Mammals are frequently exposed to various environmental stimuli, and to determine whether to approach or avoid these stimuli, the brain must assign emotional valence to them. Therefore, it is crucial to investigate the neural circuitry mechanisms involved in the mammalian brain’s processing of emotional valence. Although the central amygdala (CeA) and the ventral tegmental area (VTA) individually encode different or even opposing emotional valences, it is unclear whether there are common upstream input neurons that innervate and control both these regions, and it is interesting to know what emotional valences of these common upstream neurons. In this study, we identify three major brain regions containing neurons that project to both the CeA and the VTA, including the posterior bed nucleus of the stria terminalis (pBNST), the pedunculopontine tegmental nucleus (PPTg), and the anterior part of the basomedial amygdala (BMA). We discover that these neural populations encode distinct emotional valences. Activating neurons in the pBNST produces positive valence, enabling mice to overcome their innate avoidance behavior. Conversely, activating neurons in the PPTg produces negative valence and induces anxiety-like behaviors in mice. Neuronal activity in the BMA, on the other hand, does not influence valence processing. Thus, our study has discovered three neural populations that project to both the CeA and the VTA and has revealed the distinct emotional valences these populations encode. These results provide new insights into the neurological mechanisms involved in emotional regulation.